Research on employment support of autistic children in underdeveloped areas - Chen, Yitian; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
As a neurodevelopmental disorder, autism causes great pressure on the spirit of patients and their families. Since 1982, there are more than ten million autistic children in our country, which has become one of the social topics worth paying attention to. Because of the lifelong nature of autism, it can not be completely cured, which brings a great burden to the family economy. In addition, there are few studies on social support for autistic people in our country, there is also a lack of necessary and in-depth discussion on the employment of children with autism. With the continuous development of our country’s economy, the regional social welfare system is well established in the areas with good economic development, and autistic children in these areas can get help through relevant social remedy measures, at the same time, we can not neglect that there are many underdeveloped areas in our country, and the employment of autistic children in these areas has not been effectively and properly solved. In view of the above background, according to my own professional knowledge, through the network questionnaire and offline interviews and other research methods, summed up the current employment support of autistic children in underdeveloped areas of our country, many problems, at the same time, the paper discusses the specific reasons of the relevant problems in a deep level, and finally, on the premise of combining the reasons of the problems and referring to more academic literature, this paper puts forward some pertinent and feasible suggestions and countermeasures on how to effectively solve the employment support problem of autistic children in underdeveloped areas, so as to provide reference for relevant practitioners and social researchers.